Motif Menonton Program “I Look” Di Net TV Pada Followers Instagram @ilook_net (Jurnal Kajian Media, 2019)
Among the types of mass media, television has become one of the popular medias in Indonesia. One popular television programme is I Look, where one of the events discusses fashion. This research is expected to provide a clear understanding of the motive used by the viewers of the television on I Look programme Net TV. Motive theory with 4 dimensions (information motive, personal identity, integration, and entertainment motive) is the supporting theory in this research. Uses and gratification theory is a supporting theory, because it explains how an individual is a selective person in using the media. Respondents in this research are followers of account instagram @ilook_net. Sample technique used in this research is non probability sampling, that is quota sampling, and uses descriptive quantitative method. The results in this research found that the motive information became the main motive in watching I Look impressions; followed by the motives of entertainment, integration, and personal identity.Keywords: I look, fashion programme, motive, uses and gratification